Customer satisfaction towards Lekor Shop product: research on end users of Menara TM / Chatila @ Nur Asyhikin Jamal - Jamal, Chatila @ Nur Asyhikin (Faculty of Business and Management, 2007)
Bumiputera SME Company is getting more and more by the help of Malaysian government. As we already know, government provides several incentives to encourage the Bumiputera to open up business. Here, the research is done on one of Bumiputera SME Company which is Lekor Shop (M) Sdn. Bhd.